Rearrange first equation so we can eliminate one variable: y= - 4 -3x We can then plug this into the second equation so we get rid of the y's and just have x's: 3x-4(-3x-4)=6Simplify this: 3x + 12x+16=6 which gives 15x = -10 and then x=-10/15 = -2/3Can plug x back in to any equation to find out y, this gives: y = - 4 -3(-2/3)y= - 4 +2 so y= -2Final answer: x= -2/3 and y= -2

One to one online tuition can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor